221Evaluating the ability of different substrate mapping techniques to identify scar-related ventricular tachycardia circuits using computational modelling. (18th June 2020) - Campos, F; Orini, M; Whitaker, J; O"neill, M; Razavi, R; Porter, B; Hanson, B; Aldo Rinaldi, C; Gill, J; Lambiase, P D; Taggart, P; Bishop, M J
Abstract: Funding Acknowledgements: National Institute for Health Research; British Heart Foundation; and The Wellcome Trust and Engineering and Physical Sciences Research Council. Background: Accurate identification of targets for catheter ablation therapy of ventricular tachycardias (VTs) in the postinfarction heart remains a significant challenge. Identification of such targets often requires VT-induction to delineate the entry/exit points of the reentrant circuit sustaining the VT. However, inducibility may not be possible due to hemodynamic instability. In this scenario, substrate ablation strategies can still be performed to uncover the arrhythmogenic substrate during sinus or paced rhythm. However, substrate mapping may fail to accurately delineate the reentrant circuit resulting in VT recurrence after the procedure. Purpose: To use computer simulations to compare the ability of different electroanatomical maps constructed following typical substrate ablation strategies to identify the VT exit site. Methods: An image-based computational model of the porcine post-infarction left ventricle was constructed to simulate VT and paced rhythm. Electroanatomical maps were constructed based on the following features extracted from electrograms computed on the endocardial surface: activation time (AT), bipolar electrogram amplitude, signal fractionation and the reentry vulnerability index (RVI - a metric combining activation and repolarization timings to identify tissue susceptibility to reentry). Potential ablation targets during substrate mapping were compared for: highest 5% AT gradient; lowest 5% bipolar signal amplitudes; areas with fragmented signals (more than one peak); and lowest 5% RVI. The minimum distance, d, between the manually identified VT exit site and the targets was measured. Results: The RVI performed better than the other metrics at detecting the VT exit site (see Figure). The minimum distance between sites of lowest RVI and the exit site was 3.2mm compared to 13.1mm and 15.9mm in traditional AT and voltage maps, respectively. As the scar was not transmural, parameters derived from all electrograms (including those located on dense scar regions) were used to construct the electroanatomical maps. This improved the performance of the RVI significantly, making it more specific than the other metrics as can be seen in the Figure. Conclusions: Among all metrics investigated here, the RVI identified the vulnerable region closest to VT exit site. This finding suggests that activation-repolarization metrics may improve the detection of pro-arrhythmic regions without having to induce VT. Moreover, the RVI may be particularly well suited for detecting vulnerable regions within non-transmural scars.